Visual acuity after Gamma-Knife radiosurgery of choroidal melanomas. Issue 2 (7th November 2012) - Wackernagel, Werner; Holl, Etienne; Tarmann, Lisa; Avian, Alexander; Schneider, Mona Regina; Kapp, Karin; Langmann, Gerald
Abstract : Background/aims: To report on conservation of visual acuity after Gamma-Knife radiosurgery of choroidal melanoma. Methods: A total of 189 patients with choroidal melanoma were treated with Gamma-Knife stereotactic single-fraction radiosurgery at a single institution between June 1992 and May 2010. The main outcome measure of our retrospective analysis was conservation of pretreatment visual acuity of 20/40 or better, 20/200 or better and counting fingers (CF) or better, over time of follow-up. Patient, tumour and treatment parameters were evaluated as potential risk factors for visual loss. Results: Five years after treatment, the actuarial probability of keeping visual acuity better than 20/40, 20/200 and CF was 13%, 14% and 36%, respectively. The majority of patients (84.7%) encountered a deterioration of vision after treatment. The most important risk factors for visual loss were tumour height, longest basal diameter, distance to the optic disk and/or foveola, and retinal detachment before treatment. Treatment dose, and patient characteristics (age, sex, concurrent systemic diseases) were less important. Local tumour control rate was 94.4% after a median follow-up of 39.5 months. Conclusions: Visual outcome after single-fraction Gamma-Knife radiotherapy is comparable with linear accelerator (LINAC) based fractionated stereotactic radiotherapy, inferior to proton beam radiotherapy, and depends primarily on tumour size, location and pre-existing retinal detachment.